Environment-friendly flexible halogen-free flame-retardant cable material and preparation method thereof
Through the mixing reaction and extrusion granulation process of preparing flame retardant fillers, the flame retardant performance and flexibility problems of cable materials are solved, and efficient flame retardant performance and flexibility improvement are achieved.
Patent Information
- Application Number
- CN202511082510.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-09-12
AI Technical Summary
The flame retardant properties of existing cable materials are poor. Flame retardant fillers are prone to form stress concentration points in the cable materials, affecting the flexibility of the cable materials. In addition, flame retardant fillers are prone to moisture absorption and decomposition, resulting in a decrease in flame retardant properties.
The flame retardant filler is prepared by mixing γ-methacryloxypropyltrimethoxysilane, composite magnesium hydroxide whiskers, lauryl methacrylate and isobornyl acrylate, and is extruded and granulated by a twin-screw extruder to form a flexible network structure, thereby improving the flame retardancy and flexibility of the cable material.
It improves the flame retardant and mechanical properties of the cable material, avoids the agglomeration and hygroscopic decomposition of the flame retardant filler, enhances the flexibility and tensile strength of the cable material, and forms a uniformly dispersed carbon layer structure.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of halogen-free flame-retardant cable materials, in particular to an environmentally friendly flexible halogen-free flame-retardant cable material and a preparation method thereof. Background Art
[0002] Cables are made of one or more wires twisted together to form a conductor core, mainly composed of a core, an insulation layer, a shielding layer and a sheath layer. They are widely used in many fields such as power transmission and signal transmission. Among them, the cable materials used for the insulation layer and sheath layer of wires and cables can withstand mechanical external forces or tension and avoid damage to the wires. Polyolefins are mostly used as the cable material matrix, which has a low oxygen index and is prone to fire, causing damage to electronic and electrical equipment. In addition, when a fire occurs, a large amount of irritating and corrosive gases will be generated, which will endanger human health and hinder people's escape. Therefore, it is necessary to provide an environmentally friendly, flexible, halogen-free, flame-retardant cable material.
[0003] The cable material prepared by mixing the cable material matrix polyolefin, inorganic flame retardant filler, and organic flame retardant filler and compounding auxiliary agents can effectively improve the flame retardant properties of the cable material. However, the inorganic flame retardant filler and the organic flame retardant filler have poor compatibility with the cable material matrix polyolefin, and are prone to agglomeration and precipitation in the cable material matrix, affecting the flame retardant properties of the cable material. The agglomeration of the flame retardant filler can easily lead to the formation of stress concentration points in the cable material, affecting the flexibility of the cable material. In addition, the flame retardant filler is easy to absorb moisture and decompose, resulting in a decrease in the flame retardant properties of the cable material. Summary of the Invention
[0004] The present invention provides an environmentally friendly flexible halogen-free flame-retardant cable material and a preparation method thereof, which solves the problems that the cable material has poor flame retardancy and the flame retardant filler easily forms stress concentration points in the cable material, thereby affecting the flexibility of the cable material.
[0005] The technical solution of the present invention: An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 70-80 parts of polyolefin resin, 30-40 parts of ethylene-vinyl acetate copolymer, 15-20 parts of flame-retardant filler, 2-5 parts of heat stabilizer, 3-5 parts of antioxidant, 5-8 parts of lubricant, 1-2 parts of coupling agent, and 1-2 parts of compatibilizer; The flame retardant filler is obtained by mixing and reacting γ-methacryloxypropyltrimethoxysilane, composite magnesium hydroxide whiskers, lauryl methacrylate and isobornyl acrylate; Composite magnesium hydroxide whiskers are prepared by loading porous carbon on the surface of magnesium hydroxide whiskers, adsorbing guanyl urea phosphate, and then modifying the surface with carboxylated silicone oil. A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: The polyolefin resin, ethylene-vinyl acetate copolymer, flame retardant filler, heat stabilizer, antioxidant, lubricant, coupling agent and compatibilizer are mixed, stirred at 800-1000 r / min for 15-30 minutes, extruded through an extruder, granulated, cooled and pelletized to obtain a halogen-free flame retardant cable material.
[0006] Furthermore, the polyolefin resin is selected from any one of linear low-density polyethylene, high-density polyethylene and polypropylene.
[0007] Furthermore, the heat stabilizer is selected from any one of calcium zinc stabilizer CZ-116, calcium zinc stabilizer CZ-108 and calcium zinc stabilizer CZ-113.
[0008] Furthermore, the antioxidant is selected from any one of antioxidant 168, antioxidant 565, antioxidant 1024 and antioxidant 1010.
[0009] Furthermore, the lubricant is selected from any one of zinc stearate, calcium stearate and magnesium stearate.
[0010] Furthermore, the coupling agent is isopropyl tris(dioctyl pyrophosphate) titanate.
[0011] Furthermore, the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer.
[0012] Furthermore, the extruder is a twin-screw extruder with a feeding speed of 40-60 r / min, a screw speed of 100-400 r / min, an extrusion temperature of 165-180° C., a screw aspect ratio of (33-45):1, and a time of 2-4 h.
[0013] Furthermore, the flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol, stirred, and porous carbon was added. After continued stirring, the mixture was filtered, washed, and dried to obtain magnesium hydroxide whiskers loaded with porous carbon; A2. The guanyl urea phosphate was added to ethanol and stirred until completely dissolved. The magnesium hydroxide whiskers loaded with porous carbon were added. After stirring and adsorption was completed, the mixture was dried until the ethanol evaporated to obtain modified magnesium hydroxide whiskers. A3. The carboxylated silicone oil was added to ammonia water, stirred until completely dissolved, modified magnesium hydroxide whiskers were added, stirred, filtered, and dried to obtain composite magnesium hydroxide whiskers; A4. The composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred, γ-methacryloxypropyltrimethoxysilane was added, and the reaction was stirred. After completion of the reaction, it was cooled to room temperature, filtered, washed, and dried to obtain double-bonded composite magnesium hydroxide whiskers; A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers and stir at 80-85°C for 8-10 hours. Cool to room temperature, filter, wash, and dry to obtain a flame-retardant filler.
[0014] Furthermore, during the above-mentioned A1 reaction, the large amount of phenolic hydroxyl groups contained in tannic acid have high adhesion properties and can act as a linker to adhere porous carbon to the surface of magnesium hydroxide whiskers, so that the porous carbon adheres to the surface of magnesium hydroxide whiskers through tannic acid, thereby obtaining magnesium hydroxide whiskers loaded with porous carbon.
[0015] Furthermore, in the above-mentioned reaction process A2, ethanol is used as a solvent, and guanyl urea phosphate is dissolved in ethanol. The porous carbon structure on the surface of the magnesium hydroxide whisker loaded with porous carbon has high adsorption performance and specific surface area, and can adsorb guanyl urea phosphate into the porous carbon structure on the surface of the magnesium hydroxide whisker to obtain modified magnesium hydroxide whiskers.
[0016] Furthermore, during the above-mentioned reaction A3, the modified magnesium hydroxide whiskers are surface-modified with carboxylated silicone oil. The carboxyl groups contained in the molecular chain of the carboxylated silicone oil can be chemically bonded to the hydroxyl groups on the surface of the modified magnesium hydroxide whiskers, so that the carboxylated silicone oil is coated on the surface of the modified magnesium hydroxide whiskers to obtain composite magnesium hydroxide whiskers.
[0017] Furthermore, during the above reaction A4, the silanol groups generated by the hydrolysis of γ-methacryloxypropyltrimethoxysilane can be chemically bonded to the carboxyl groups on the surface of the composite magnesium hydroxide whiskers, so that the composite magnesium hydroxide whiskers carry reactive double bonds.
[0018] Furthermore, in the above-mentioned A5 reaction process, dibenzoyl peroxide is used as an initiator and acetone is used as a solvent, so that lauryl methacrylate, isobornyl acrylate and the double bonds carried by the composite magnesium hydroxide whiskers undergo copolymerization reaction, thereby forming a flexible network structure on the surface of the composite magnesium hydroxide whiskers to obtain a flame retardant filler.
[0019] Furthermore, in step A1, the mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol and porous carbon is (2-2.6):(0.2-0.7):(65-75):(1.5-2).
[0020] Furthermore, in step A2, the mass ratio of guanyl urea phosphate, ethanol and porous carbon-loaded magnesium hydroxide whiskers is (1.3-1.5):(20-25):(2-4).
[0021] Furthermore, in step A3, the mass ratio of carboxylated silicone oil, ammonia water and modified magnesium hydroxide whiskers is (0.8-1.2):(35-40):(2.6-3).
[0022] Furthermore, in step A4, the mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water and γ-methacryloxypropyltrimethoxysilane is (2.5-3.5):(55-60):(18-22):(1-2).
[0023] Furthermore, in step A5, the mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers is (1-2):(0.8-1.2):(40-50):(0.1-0.3):(3.1-3.5).
[0024] The present invention has the following beneficial effects: (1) In the technical solution of the present invention, a porous carbon structure is loaded on the surface of magnesium hydroxide whiskers. On the one hand, magnesium hydroxide whiskers, as inorganic flame retardants, can absorb heat in the cable material during combustion and reduce the reaction temperature. The heat absorption is accompanied by the degradation of magnesium hydroxide whiskers, and the released water vapor can dilute the flame, which has high flame retardant properties. On the other hand, the porous carbon structure has high acid resistance, which can improve the acid resistance of magnesium hydroxide whiskers and avoid the degradation of alkaline magnesium hydroxide whiskers under acidic conditions, which affects the flame retardant properties. In addition, the porous carbon structure has a smoking effect, which reduces the generation of a large amount of irritating and corrosive gases in fires. In addition, magnesium hydroxide whiskers have an excellent aspect ratio and are dispersed in the cable material to improve the mechanical properties of the cable material.
[0025] (2) In the technical solution of the present invention, guanyl urea phosphate is adsorbed into the porous carbon structure on the surface of magnesium hydroxide whiskers. Guanyl urea phosphate is a phosphorus-based flame retardant. The nitrogen and phosphorus elements contained in guanyl urea phosphate can produce non-combustible gas and capture free radicals during combustion to inhibit combustion, and has good flame retardant properties. In addition, magnesium hydroxide whiskers have a high aspect ratio and specific surface area. As a carrier of guanyl urea phosphate, it improves the dispersibility of guanyl urea phosphate in cable materials and avoids the agglomeration of guanyl urea phosphate in cable materials, resulting in uneven flame retardant effect. In addition, during the combustion process, guanyl urea phosphate can catalyze the cable material matrix polyolefin to form a carbon layer. The fibrous structure formed by the thermal decomposition of magnesium hydroxide whiskers is dispersed in the carbon layer structure, thereby improving the density of the carbon layer. The fibrous structure serves as the supporting skeleton of the carbon layer, which can effectively prevent the carbon layer from being brittle and prone to cracking, thereby improving the flame retardant properties of the cable material.
[0026] (3) In the technical solution of the present invention, the surface of the modified magnesium hydroxide whisker is modified by carboxylated silicone oil, and a large number of long-chain structures with silicon-oxygen-silicon bonds are formed on the surface of the modified magnesium hydroxide whisker, which has high ductility, softness and good hydrophobicity, can inhibit the water absorption of guanyl urea phosphate, avoid the guanyl urea phosphate in the modified magnesium hydroxide whisker from easily absorbing moisture and causing the flame retardant performance to decrease, and improve the toughness of the cable material. In addition, guanyl urea phosphate and the silicon element in the carboxylated silicone oil form a nitrogen-phosphorus-silicon ternary flame retardant, which significantly improves the flame retardant performance of the cable material.
[0027] (4) In the technical solution of the present invention, the double bonds carried by lauryl methacrylate, isobornyl acrylate and composite magnesium hydroxide whiskers undergo copolymerization reaction, and then a flexible network structure is formed on the surface of the composite magnesium hydroxide whiskers. The formed flexible network structure can improve the flexibility and mechanical properties of the cable material, avoid the addition of flame retardant fillers, which leads to embrittlement, decreased tensile strength and toughness of the cable material, and the tough chain structure carried by lauryl methacrylate can improve the flexibility of the cable material. The large bridge ring side group carried by isobornyl acrylate can increase the spatial steric hindrance of the cable material matrix polyolefin, limit the close stacking between molecular chains, and improve the flexibility of the material. In addition, the flexible network structure formed by lauryl methacrylate, isobornyl acrylate and γ-methacryloyloxypropyltrimethoxysilane has good compatibility with the cable material matrix polyolefin, so that the composite flame retardant filler is evenly dispersed in the cable material, thereby improving the flame retardancy, flexibility and tensile properties of the cable material. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0029] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0030] Among them, the polyolefin resin is linear low-density polyethylene with a specific gravity of 0.916g / cm 3 , the melt index is 3.2g / 10min under ASTM D1238 test standard.
[0031] Ethylene-vinyl acetate copolymer, brand EVA180F, purchased from Shanghai Ren En Import and Export Trading Co., Ltd. The heat stabilizer is calcium zinc stabilizer CZ-116, the antioxidant is antioxidant 168, the lubricant is zinc stearate, and the coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.
[0032] The compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, brand 3126, Dongguan Sujia Polymer Raw Materials Co., Ltd.
[0033] Magnesium hydroxide whiskers with a diameter of 3 μm and a length of 45 μm were purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.
[0034] The porous carbon has a pore size of 50 nm, product number: 103050, and was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.
[0035] Carboxylated silicone oil is specifically prepared by the following steps: 40 g of toluene, 20 g of polymethylhydrogensiloxane, 0.03 g of chloroplatinic acid hexahydrate and 5 g of isopropanol were mixed evenly, nitrogen was introduced, 30 g of methyl methacrylate was added, and the mixture was stirred at 80 ° C for 1.5 h and at 140 ° C for 30 h. After removing the solvent by reduced pressure distillation, the mixture was washed with ethanol 3 times, and the product was collected by centrifugation at 1000 r / min. The product was mixed with 100 g of 10% sodium hydroxide aqueous solution by mass, hydrolyzed at 100 ° C for 2 h to fractionate methanol, and 36% hydrochloric acid was added to adjust the pH to 6 to precipitate a white solid. The white solid was washed 3 times with deionized water and dried in vacuo at 60 ° C for 12 h to obtain carboxylated silicone oil.
[0036] Example 1 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 70 parts of linear low-density polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 15 parts of flame-retardant filler, 2 parts of calcium zinc stabilizer CZ-116, 3 parts of antioxidant 168, 5 parts of zinc stearate, 1 part of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 1 part of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 800 r / min for 15 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 40 r / min, a screw speed of 100 r / min, an extrusion temperature of 165° C., a screw length-diameter ratio of 33:1, and a time of 2 h.
[0037] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for another 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain porous carbon-loaded magnesium hydroxide whiskers. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2:0.2:65:1.5. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.3:20:2. A3. Add carboxylated silicone oil to 5% ammonia water and stir until completely dissolved. Then add modified magnesium hydroxide whiskers and stir at 50°C for 20 minutes. Filter and dry in a 60°C oven for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers is 0.8:35:2.6. A4. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in a 70°C oven for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers. The mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 2.5:55:18:1. A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 80°C for 8 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 1:0.8:40:0.1:3.1.
[0038] Example 2 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 75 parts of linear low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of flame-retardant filler, 3 parts of calcium zinc stabilizer CZ-116, 4 parts of antioxidant 168, 7 parts of zinc stearate, 1.5 parts of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, and 1.5 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 900 r / min for 23 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 50 r / min, a screw speed of 250 r / min, an extrusion temperature of 170°C, a screw length-diameter ratio of 40:1, and a time of 3 h.
[0039] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain magnesium hydroxide whiskers loaded with porous carbon. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2.3:0.5:70:1.8. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.4:23:3. A3. Add carboxylated silicone oil to 5% ammonia water and stir until completely dissolved. Then add modified magnesium hydroxide whiskers and stir at 50°C for 20 minutes. Filter and dry in a 60°C oven for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers is 1:38:2.8. A4. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in a 70°C oven for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers. The mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3:58:20:1.5. A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 83°C for 9 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 1.5:1:45:0.2:3.3.
[0040] Example 3 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0041] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain magnesium hydroxide whiskers loaded with porous carbon. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2.6:0.7:75:2. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.5:25:4. A3. Carboxylated silicone oil was added to 5% ammonia water and stirred until completely dissolved. Modified magnesium hydroxide whiskers were then added and stirred at 50°C for 20 minutes. The mixture was filtered and dried in an oven at 60°C for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers was 1.2:40:3. A4. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers. The mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3.5:60:22:2. A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 2:1.2:50:0.3:3.5.
[0042] Comparative Example 1 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0043] The flame retardant filler is specifically prepared by the following steps: A1. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers were then added and stirred at 60°C for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and magnesium hydroxide whiskers was 1.5:25:4. A2. Add carboxylated silicone oil to 5% ammonia water and stir until completely dissolved. Then add modified magnesium hydroxide whiskers and stir at 50°C for 20 minutes. Filter and dry in a 60°C oven for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers is 1.2:40:3. A3. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in a 70°C oven for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers; the mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3.5:60:22:2; A4. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 2:1.2:50:0.3:3.5.
[0044] Comparative Example 2 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0045] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide particles (45 μm in size, purchased from Gongyi Qianghong Water Purification Materials Co., Ltd.) and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in a 70°C oven for 10 minutes to obtain porous carbon-loaded magnesium hydroxide whiskers. The mass ratio of magnesium hydroxide particles, tannic acid, ethanol, and porous carbon was 2.6:0.7:75:2. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide particles loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide particles. The mass ratio of guanylurea phosphate, ethanol, and porous carbon loaded magnesium hydroxide particles was 1.5:25:4. A3. Carboxylated silicone oil was added to 5% ammonia water and stirred until completely dissolved. Modified magnesium hydroxide particles were added and stirred at 50°C for 20 minutes. The mixture was filtered and dried in an oven at 60°C for 12 hours to obtain composite magnesium hydroxide particles. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide particles was 1.2:40:3. A4. The composite magnesium hydroxide particles were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The reaction was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in a 70°C oven for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers; the mass ratio of composite magnesium hydroxide particles, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3.5:60:22:2; A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide particles. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide particles is 2:1.2:50:0.3:3.5.
[0046] Comparative Example 3 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0047] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain magnesium hydroxide whiskers loaded with porous carbon. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2.6:0.7:75:2. A2. Phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.5:25:4. A3. Carboxylated silicone oil was added to 5% ammonia water and stirred until completely dissolved. Modified magnesium hydroxide whiskers were then added and stirred at 50°C for 20 minutes. The mixture was filtered and dried in an oven at 60°C for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers was 1.2:40:3. A4. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers. The mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3.5:60:22:2. A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 2:1.2:50:0.3:3.5.
[0048] Comparative Example 4 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0049] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain magnesium hydroxide whiskers loaded with porous carbon. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2.6:0.7:75:2. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.5:25:4. A3. Modified magnesium hydroxide whiskers were added to ethanol and deionized water and stirred uniformly. γ-Methacryloxypropyltrimethoxysilane was then added and stirred at 70°C for 1.5 hours. The mixture was cooled to room temperature, filtered, washed three times with ethanol and three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain double-bonded magnesium hydroxide whiskers. The mass ratio of modified magnesium hydroxide whiskers, ethanol, deionized water, and γ-Methacryloxypropyltrimethoxysilane was 3.5:60:22:2. A4. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded magnesium hydroxide whiskers. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded magnesium hydroxide whiskers is 2:1.2:50:0.3:3.5.
[0050] Comparative Example 5 An environmentally friendly flexible halogen-free flame-retardant cable material, comprising the following raw materials in parts by weight: 80 parts of linear low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 20 parts of flame-retardant filler, 5 parts of calcium zinc stabilizer CZ-116, 5 parts of antioxidant 168, 8 parts of zinc stearate, 2 parts of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and 2 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer; A method for preparing an environmentally friendly flexible halogen-free flame-retardant cable material comprises the following steps: Linear low-density polyethylene, ethylene-vinyl acetate copolymer, flame retardant filler, calcium zinc stabilizer CZ-116, antioxidant 168, zinc stearate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, and maleic anhydride grafted ethylene-vinyl acetate copolymer were mixed, stirred at 1000 r / min for 30 min, extruded through an extruder, granulated, cooled, and pelletized to obtain a halogen-free flame retardant cable material; The extruder is a twin-screw extruder with a feed rate of 60 r / min, a screw speed of 400 r / min, an extrusion temperature of 180°C, a screw length-diameter ratio of 45:1, and a time of 4 h.
[0051] The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol and stirred at 60°C for 30 minutes. Porous carbon was then added and stirred for 10 minutes. The mixture was filtered, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain magnesium hydroxide whiskers loaded with porous carbon. The mass ratio of magnesium hydroxide whiskers, tannic acid, ethanol, and porous carbon was 2.6:0.7:75:2. A2. Guanylurea phosphate was added to ethanol and stirred until completely dissolved. Magnesium hydroxide whiskers loaded with porous carbon were then added and adsorbed at 60°C with stirring for 30 minutes. The mixture was then dried in an oven at 80°C until the ethanol evaporated, yielding modified magnesium hydroxide whiskers. The mass ratio of guanylurea phosphate, ethanol, and porous carbon-loaded magnesium hydroxide whiskers was 1.5:25:4. A3. Carboxylated silicone oil was added to 5% ammonia water and stirred until completely dissolved. Modified magnesium hydroxide whiskers were then added and stirred at 50°C for 20 minutes. The mixture was filtered and dried in an oven at 60°C for 12 hours to obtain composite magnesium hydroxide whiskers. The mass ratio of carboxylated silicone oil, ammonia water, and modified magnesium hydroxide whiskers was 1.2:40:3. A4. Composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred uniformly, and γ-methacryloxypropyltrimethoxysilane was added. The mixture was stirred at 70°C for 1.5 hours, cooled to room temperature, filtered, washed three times with ethanol, washed three times with deionized water, and dried in an oven at 70°C for 10 minutes to obtain double-bonded composite magnesium hydroxide whiskers. The mass ratio of composite magnesium hydroxide whiskers, ethanol, deionized water, and γ-methacryloxypropyltrimethoxysilane was 3.5:60:22:2. A5. Add isobornyl acrylate to acetone and stir evenly. Then add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers. Stir and react at 85°C for 10 hours. Cool to room temperature, filter, wash three times with deionized water, and dry in an oven at 80°C for 10 minutes to obtain a flame-retardant filler. The mass ratio of isobornyl acrylate, acetone, dibenzoyl peroxide, and double-bonded composite magnesium hydroxide whiskers is 3.2:50:0.3:3.5.
[0052] The performance of the halogen-free flame retardant cable materials prepared in Examples 1-3 and Comparative Examples 1-5 was tested.
[0053] Mechanical property testing: The tensile strength and elongation at break of the halogen-free flame retardant cable material prepared above were tested according to GB / T1040-1992 standard.
[0054] Flame retardant performance testing: The flame retardant performance of the halogen-free flame retardant cable material prepared above was tested in accordance with GB / T2406.1-2008 standard.
[0055] As shown in Table 1 below.
[0056] Table 1 Performance test of halogen-free flame retardant cable materials prepared in Examples 1-3 and Comparative Examples 1-5
[0057] It can be seen from the data in Table 1 that the halogen-free flame retardant cable materials prepared in Examples 1-3 have relatively high flame retardant properties and mechanical properties.
[0058] In Comparative Example 1, the magnesium hydroxide whiskers loaded with porous carbon were replaced with flame-retardant fillers prepared from magnesium hydroxide whiskers and added to the halogen-free flame-retardant cable material. The flame retardant properties and mechanical properties decreased, proving that the porous carbon structure loaded on the surface of the magnesium hydroxide whiskers has high acid resistance, can improve the acid resistance of the magnesium hydroxide whiskers, and avoid the degradation of the alkaline magnesium hydroxide whiskers under acidic conditions, which affects the flame retardant properties. In addition, the magnesium hydroxide whiskers have an excellent aspect ratio and are dispersed in the cable material to improve the mechanical properties of the cable material.
[0059] In Comparative Example 2, the flame retardant filler prepared by replacing the magnesium hydroxide whiskers with magnesium hydroxide particles was added to the halogen-free flame retardant cable material. Its flame retardant properties and mechanical properties decreased, proving that magnesium hydroxide whiskers, as an inorganic flame retardant, can absorb heat in the cable material, reduce the reaction temperature, and release water vapor to dilute the flame, and have high flame retardant properties. The fibrous structure formed by the thermal decomposition of the magnesium hydroxide whiskers is dispersed in the carbon layer structure, thereby improving the density of the carbon layer and the flame retardant properties of the cable material.
[0060] In Comparative Example 3, a flame retardant filler prepared by replacing guanyl urea phosphate with phosphate ester was added to a halogen-free flame retardant cable material, and its flame retardant performance decreased. This proves that guanyl urea phosphate, as a phosphorus-based flame retardant, contains nitrogen and phosphorus elements, which can produce non-combustible gases and capture free radicals during combustion to inhibit combustion, and has good flame retardant properties. It can also form a nitrogen-phosphorus-silicon ternary flame retardant with the silicon element in the carboxylated silicone oil, significantly improving the flame retardant properties of the cable material.
[0061] In Comparative Example 4, the flame retardant filler prepared by replacing the composite magnesium hydroxide whiskers with modified magnesium hydroxide whiskers was added to the halogen-free flame retardant cable material, and its flame retardant properties and mechanical properties decreased, proving that the surface of the modified magnesium hydroxide whiskers was modified by carboxylated silicone oil, and a large number of long-chain structures with silicon-oxygen-silicon bonds were formed on the surface of the modified magnesium hydroxide whiskers, which had high ductility, softness and good hydrophobicity, could inhibit the water absorption of guanyl urea phosphate, and improved the toughness of the cable material. In addition, it could form a nitrogen-phosphorus-silicon ternary flame retardant with guanyl urea phosphate, significantly improving the flame retardant properties of the cable material.
[0062] In Comparative Example 5, the flame retardant filler prepared by replacing lauryl methacrylate with isobornyl acrylate was added to the halogen-free flame retardant cable material, and its flame retardant properties and mechanical properties decreased, proving that lauryl methacrylate, isobornyl acrylate and the double bonds carried by the composite magnesium hydroxide whiskers undergo copolymerization to form a flexible network structure on the surface of the composite magnesium hydroxide whiskers, thereby improving the flexibility and mechanical properties of the cable material. The flexible network structure has good compatibility with the cable material matrix polyolefin, so that the composite flame retardant filler is evenly dispersed in the cable material, thereby improving the flame retardancy, flexibility and tensile properties of the cable material.
[0063] Throughout the specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. An environmentally friendly flexible halogen-free flame-retardant cable material, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of polyolefin resin, 30-40 parts of ethylene-vinyl acetate copolymer, 15-20 parts of flame retardant filler, 2-5 parts of heat stabilizer, 3-5 parts of antioxidant, 5-8 parts of lubricant, 1-2 parts of coupling agent and 1-2 parts of compatibilizer; The flame retardant filler is obtained by mixing and reacting γ-methacryloxypropyltrimethoxysilane, composite magnesium hydroxide whiskers, lauryl methacrylate and isobornyl acrylate; The composite magnesium hydroxide whisker is obtained by loading porous carbon on the surface of magnesium hydroxide whisker, adsorbing guanyl urea phosphate, and then modifying the surface with carboxylated silicone oil.
2. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 1, characterized in that: The flame retardant filler is specifically prepared by the following steps: A1. Magnesium hydroxide whiskers and tannic acid were added to ethanol, stirred, and porous carbon was added. After continued stirring, the mixture was filtered, washed, and dried to obtain magnesium hydroxide whiskers loaded with porous carbon; A2. The guanyl urea phosphate was added to ethanol and stirred until completely dissolved. The magnesium hydroxide whiskers loaded with porous carbon were added. After stirring and adsorption was completed, the mixture was dried until the ethanol evaporated to obtain modified magnesium hydroxide whiskers. A3. The carboxylated silicone oil was added to ammonia water, stirred until completely dissolved, modified magnesium hydroxide whiskers were added, stirred, filtered, and dried to obtain composite magnesium hydroxide whiskers; A4. The composite magnesium hydroxide whiskers were added to ethanol and deionized water, stirred, γ-methacryloxypropyltrimethoxysilane was added, and the reaction was stirred. After completion of the reaction, it was cooled to room temperature, filtered, washed, and dried to obtain double-bonded composite magnesium hydroxide whiskers; A5. Add lauryl methacrylate and isobornyl acrylate to acetone and stir evenly. Add dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers and stir at 80-85°C for 8-10 hours. Cool to room temperature, filter, wash, and dry to obtain a flame-retardant filler.
3. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 2, characterized in that: In step A1, the mass ratio of the magnesium hydroxide whiskers, tannic acid, ethanol and porous carbon is (2-2.6):(0.2-0.7):(65-75):(1.5-2).
4. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 2, characterized in that: In step A2, the mass ratio of the guanyl urea phosphate, ethanol and the porous carbon-loaded magnesium hydroxide whiskers is (1.3-1.5):(20-25):(2-4).
5. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 2, characterized in that: In step A3, the mass ratio of the carboxylated silicone oil, ammonia water and modified magnesium hydroxide whiskers is (0.8-1.2):(35-40):(2.6-3).
6. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 2, characterized in that: In step A4, the mass ratio of the composite magnesium hydroxide whiskers, ethanol, deionized water and γ-methacryloxypropyltrimethoxysilane is (2.5-3.5):(55-60):(18-22):(1-2).
7. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 2, characterized in that: In step A5, the mass ratio of lauryl methacrylate, isobornyl acrylate, acetone, dibenzoyl peroxide and double-bonded composite magnesium hydroxide whiskers is (1-2):(0.8-1.2):(40-50):(0.1-0.3):(3.1-3.5).
8. The environmentally friendly flexible halogen-free flame-retardant cable material according to claim 1, characterized in that: The polyolefin resin is selected from any one of linear low-density polyethylene, high-density polyethylene and polypropylene.
9. A method for preparing the environmentally friendly flexible halogen-free flame-retardant cable material according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: The polyolefin resin, ethylene-vinyl acetate copolymer, flame retardant filler, heat stabilizer, antioxidant, lubricant, coupling agent and compatibilizer are mixed, stirred at 800-1000 r / min for 15-30 minutes, extruded through an extruder, granulated, cooled and pelletized to obtain a halogen-free flame retardant cable material.
Citation Information
Cited By
Ultrahigh flexible robot cable
CN121034721A